filmov
tv
Find the `sum_(r=0)^n (n+r)C_r`
Показать описание
Doubtnut
Рекомендации по теме
0:06:51
If `a_n=sum(r=0)^n 1/^nC_r, then sum _(r=0^n r/^nC_r` equals (A) `(n-1)a_n` (B) `na_n` (C) `1/2na_n`
0:03:47
The value of `sum_(r=0)^(n-1)(nC_r)/(nC_r+^n C_(r+1))` is eqaul to
0:02:13
Prove that Sum((-1)^n * (n choose r)) = 0
0:03:13
The value of `sum_(r=0)^n sum_(s=1)^n .^nC_5 .^sC_r ` is
0:01:44
Prove that `sum_(r=0)^n^n C_r3^r=4^n`
0:03:15
If `a_n=sum(1/C(n,r)` from r=0 to n, then `sum(r/C(n,r))` from r=0 to n is
0:01:40
Prove that Sum(n choose r) = 2^n
0:03:36
If `a_n=sum_(r=0)^n1/(nC_r),` then `sum_(r=0)^n r/(nC_r)` equals
0:08:48
`sum_(r=0)^n(-2)^r*(nC_r)/((r+2)C_r)` is equal to
0:06:05
If n is an even natural number, then `sum_(r=0)^n (-1)^r/(.^nC_r)` equals
0:05:34
The sum of the series ` sum_(r=0) ^(n) 'r.'^(2n)C_(r), ` is
0:04:45
IIT JEE BINOMIAL THEOREM Prove that `sum_(r=0)^n r(n-r)C r2=n^2(^(2n-2)C_n)dot`
0:03:07
The value of `sum_(r=0)^(n) r(n -r) (''^(n)C_(r))^(2)` is equal to
0:02:28
The value of `sum_(r=0)^(n-1)^n C_r//(^n C_r+^n C_(r+1))` equals a. `n+1` b. `n//2` c. ...
0:08:16
Proof by Induction : Sum of series ∑r² | ExamSolutions
0:05:35
IIT JEE BINOMIAL THEOREM Prove that `sum_(r=0)^n^n C_rsinr xcos(n-r)x=2^(n-1)sin(n x)dot`
0:03:51
The sum of the series ` sum_(r=0) ^(n) ''^(2n)C_(r), ` is
0:20:24
Summation Formulas and Sigma Notation - Calculus
0:02:48
Find the sum of `sum_(r=1)^n(r^n C_r)/(^n C_(r-1)` .
0:08:40
Prove by mathematical induction that `sum_(r=0)^(n)r^(n)C_(r)=n.2^(n-1), forall n in N`.
0:09:19
Calculus Help: Find the Sum of series sum {r=1 , n} ( (r^2+1)r! ) - National University of Singapore
0:02:54
`sum_(r=0)^n((n-3r+1)^n C_r)/((n-r+1)2^r)` is equal to
0:03:53
Finding the sum or an arithmetic series using summation notation
0:02:13
IIT JEE SEQUENCES AND SERIES The value of `sum_(r=0)^n(a+r+a r)(-a)^r` is equal to `(-1)^n[(n+1)a...